GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 10 Dec 2019, 07:06 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  # If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x

Author Message
Intern  Joined: 16 Dec 2018
Posts: 6
If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x  [#permalink]

### Show Tags

2 00:00

Difficulty:   95% (hard)

Question Stats: 42% (02:13) correct 58% (02:34) wrong based on 79 sessions

### HideShow timer Statistics

If m and n are integers and x*y is defined as $$(–1)^x + (–1)^y + (–1)^x* (–1)^y$$, then what is the value of m*n?

(1) $$m*n = 2 + (–1)^m*(–1)^n$$

(2) $$(–1)^m*(–1)^n = 1$$
Manager  B
Joined: 01 May 2017
Posts: 83
Location: India
Re: If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x  [#permalink]

### Show Tags

1) $$m*n = (-1)^m + (-1)^n + (-1)^m.(-1)^n$$ as per the question
But given,
$$m*n = 2 + (-1)^m.(-1)^n$$
Which implies $$(-1)^m = (-1)^n = 1$$
Which in turn implies m and n are even
m*n = 3
Sufficient

2)$$(-1)^m.(-1)^n = 1$$
If both mand n are even or odd this is true
If both m & n are even m*n = 3
If both m & n are odd m* n = 1
Not sufficient

Hence correct option is A

Posted from my mobile device
Director  V
Joined: 28 Jul 2016
Posts: 675
Location: India
Concentration: Finance, Human Resources
GPA: 3.97
WE: Project Management (Investment Banking)
Re: If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x  [#permalink]

### Show Tags

Mahimab wrote:
If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x · (– 1)^y, then what is the value of m*n?
(1) m*n = 2 + [(–1)^m · (–1)^n]
(2) (–1)^m· (–1)^n = 1

Can you edit the question to correct form :
Manager  B
Joined: 04 Oct 2017
Posts: 73
Re: If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x  [#permalink]

### Show Tags

[quote="Dare Devil"]1) $$m*n = (-1)^m + (-1)^n + (-1)^m.(-1)^n$$ as per the question
But given,
$$m*n = 2 + (-1)^m.(-1)^n$$
Which implies $$(-1)^m = (-1)^n = 1$$
Which in turn implies m and n are even
m*n = 3
Sufficient

2)$$(-1)^m.(-1)^n = 1$$
If both mand n are even or odd this is true
If both m & n are even m*n = 3
If both m & n are odd m* n = 1
Not sufficient

Hence correct option is A

Hi,

Can you please explain how you got (-1) to the power of m = ( -1) to the power of n = 1?

Thank you.
Manager  B
Joined: 01 May 2017
Posts: 83
Location: India
Re: If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x  [#permalink]

### Show Tags

Kezia9 wrote:
Dare Devil wrote:
1) $$m*n = (-1)^m + (-1)^n + (-1)^m.(-1)^n$$ as per the question
But given,
$$m*n = 2 + (-1)^m.(-1)^n$$
Which implies $$(-1)^m = (-1)^n = 1$$
Which in turn implies m and n are even
m*n = 3
Sufficient

2)$$(-1)^m.(-1)^n = 1$$
If both mand n are even or odd this is true
If both m & n are even m*n = 3
If both m & n are odd m* n = 1
Not sufficient

Hence correct option is A

Hi,

Can you please explain how you got (-1) to the power of m = ( -1) to the power of n = 1?

Thank you.

$$m*n = 2 + (-1)^m.(-1)^n$$

$$(-1)^m$$ OR $$(-1)^n$$ can be either 1 OR -1, since m, n are integers (may be positive or negative)
Since this is given,
$$m*n = 2 + (-1)^m.(-1)^n$$ ------ equation 1

$$m*n = (-1)^m + (-1)^n + (-1)^m.(-1)^n$$ as per the question [x,y replaced with m and n]
$$m*n = (-1)^m + (-1)^n + (-1)^m.(-1)^n$$ -------- equation 2
from equation 1 and equation 2
we know that $$(-1)^m + (-1)^n = 2$$
Since $$(-1)^(integer)$$ can only be 1 OR -1
possibilities of $$(-1)^m + (-1)^n$$ can be (0,-2,2)
Since from equation 1 and equation 2 we have deduced $$(-1)^m + (-1)^n$$ as 2, both m,n are even, which in turn implies $$(-1)^m$$ (which can be either 1 OR -1) is 1 and same for $$(-1)^n$$

I Hope this is clear
Manager  B
Joined: 04 Oct 2017
Posts: 73
Re: If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x  [#permalink]

### Show Tags

Dare Devil wrote:
Kezia9 wrote:
Dare Devil wrote:
1) $$m*n = (-1)^m + (-1)^n + (-1)^m.(-1)^n$$ as per the question
But given,
$$m*n = 2 + (-1)^m.(-1)^n$$
Which implies $$(-1)^m = (-1)^n = 1$$
Which in turn implies m and n are even
m*n = 3
Sufficient

2)$$(-1)^m.(-1)^n = 1$$
If both mand n are even or odd this is true
If both m & n are even m*n = 3
If both m & n are odd m* n = 1
Not sufficient

Hence correct option is A

Hi,

Can you please explain how you got (-1) to the power of m = ( -1) to the power of n = 1?

Thank you.

$$m*n = 2 + (-1)^m.(-1)^n$$

$$(-1)^m$$ OR $$(-1)^n$$ can be either 1 OR -1, since m, n are integers (may be positive or negative)
Since this is given,
$$m*n = 2 + (-1)^m.(-1)^n$$ ------ equation 1

$$m*n = (-1)^m + (-1)^n + (-1)^m.(-1)^n$$ as per the question [x,y replaced with m and n]
$$m*n = (-1)^m + (-1)^n + (-1)^m.(-1)^n$$ -------- equation 2
from equation 1 and equation 2
we know that $$(-1)^m + (-1)^n = 2$$
Since $$(-1)^(integer)$$ can only be 1 OR -1
possibilities of $$(-1)^m + (-1)^n$$ can be (0,-2,2)
Since from equation 1 and equation 2 we have deduced $$(-1)^m + (-1)^n$$ as 2, both m,n are even, which in turn implies $$(-1)^m$$ (which can be either 1 OR -1) is 1 and same for $$(-1)^n$$

I Hope this is clear

Thank you for the prompt reply. I understood in part. m and n are even. I got this How can we conclude m*n = 3?Product of mn could be be multiple of 2.
Manager  B
Joined: 01 May 2017
Posts: 83
Location: India
Re: If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x  [#permalink]

### Show Tags

1
Kezia9 wrote:
Dare Devil wrote:
1) $$m*n = (-1)^m + (-1)^n + (-1)^m.(-1)^n$$ as per the question
But given,
$$m*n = 2 + (-1)^m.(-1)^n$$
Which implies $$(-1)^m = (-1)^n = 1$$
Which in turn implies m and n are even
m*n = 3
Sufficient

2)$$(-1)^m.(-1)^n = 1$$
If both mand n are even or odd this is true
If both m & n are even m*n = 3
If both m & n are odd m* n = 1
Not sufficient

Hence correct option is A

Hi,

Can you please explain how you got (-1) to the power of m = ( -1) to the power of n = 1?

Thank you.

m,n are integers

Case (a)
$$(-1)^m$$ = 1 if m is even
let the even integer be 4
(negative integer)^(even) = positive
$$(-1) ^4$$ = 1

Case (b)
$$if m is odd$$ (let it be 3)
$$(-1)^-3 = (-1/1)^3 =>(-1)^3$$ = -1
(negative integer)^(odd) = negative

Lets consider 3 cases,

Case(i)
m,n both are even
then from case (a)
$$(-1)^m + (-1)^n$$ = 1 + 1 = 2
which in turn implies
$$(-1)^m*(-1)^n$$ = 1*1 = 1 as m,n are even and from Case (a)

this implies $$m∗n=(−1)^m+(−1)^n+(−1)^m*(−1)^n$$ = 2+1 =3

case(ii)
m - even and n - odd OR m -odd and n - even
$$(-1)^m$$ = 1 (if m even, from case (a))
$$(-1)^n$$= -1 ( if n odd, from case (b))
So, $$(-1)^m + (-1)^n$$ = 1-1 = 0

Case(iii)
m,n both odd (from case (b))
($$-1)^m = (-1)^n$$ = -1 ($$(-1)^3$$ = -1)
So, $$(-1)^m + (-1)^n$$ = -1-1 = -2
Manager  P
Status: wake up with a purpose
Joined: 24 Feb 2017
Posts: 154
Concentration: Accounting, Entrepreneurship
Re: If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x  [#permalink]

### Show Tags

Mahimab wrote:
If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x · (– 1)^y, then what is the value of m*n?
(1) m*n = 2 + [(–1)^m · (–1)^n]
(2) (–1)^m· (–1)^n = 1

Bunuel Would you please explain this question? I don't understand explanations above.

Posted from my mobile device
_________________
If people are NOT laughing at your GOALS, your goals are SMALL.
Director  V
Joined: 24 Oct 2016
Posts: 586
GMAT 1: 670 Q46 V36 GMAT 2: 690 Q47 V38 If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x  [#permalink]

### Show Tags

globaldesi wrote:
Mahimab wrote:
If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x · (– 1)^y, then what is the value of m*n?
(1) m*n = 2 + [(–1)^m · (–1)^n]
(2) (–1)^m· (–1)^n = 1

Can you edit the question to correct form :

Bunuel

I believe there's a typo in this Q. I think it should be "m*n is defined as" instead of "x*y is defined as". Can you please correct it? Thanks! If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x   [#permalink] 17 Mar 2019, 05:57
Display posts from previous: Sort by

# If m and n are integers and x*y is defined as (–1)^x + (–1)^y + (–1)^x  